Sealing film for electronic device
The encapsulating film for electronic devices addresses the challenge of achieving high transparency and strong adhesion by using a laminated structure with an isobutylene polymer and metal chelate compound-based adhesive layer, ensuring effective moisture and oxygen barrier properties.
Patent Information
- Application Number
- JP2023166563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
Existing encapsulating films for electronic devices with high inorganic filler content face challenges in achieving sufficient adhesion and high transparency, making them unsuitable for electronic devices requiring higher transparency.
A laminated encapsulating film structure featuring a gas barrier layer made of an inorganic material and an adhesive layer containing an isobutylene polymer and a metal chelate compound, with a haze rate of 10% or less, ensuring strong adhesion and high transparency.
The encapsulating film provides excellent adhesion between the barrier layer and the adhesive layer, maintaining low humidity and oxygen conditions while offering high transparency, suitable for electronic devices with transparency requirements.
Smart Images

Figure 2025056984000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealing film for electronic devices. [Background technology]
[0002] As a sealing composition and a sealing film suitable for sealing electronic elements in a flexible electronic device, a sealing composition containing the following components (A) to (C) and a sealing film obtained by applying the sealing composition onto a release-treated PET film and drying the composition are known (see Patent Document 1). (A) Polyolefin resin and / or polyolefin rubber (B) Inorganic filler (C) Metal complexes in which a bidentate ligand in which both coordinating atoms are oxygen atoms and a monodentate ligand in which the coordinating atom is an oxygen atom are bonded to a central metal A silane coupling agent is described as a surface treatment agent for the inorganic filler.
[0003] Furthermore, it is described that the above-mentioned sealing sheet is laminated on the inorganic film surface of a barrier film having an inorganic film (SiO2 film) formed on a cycloolefin polymer film using a batch type vacuum laminator to obtain a laminated film, and the PET film of the sealing sheet that has been release-treated with a silicone-based release treatment agent is peeled off, and a polyimide film is laminated on the exposed composition layer using a batch type vacuum laminator to obtain a laminated film A that has excellent bending resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019-189723 Summary of the Invention [Problem to be solved by the invention]
[0005] However, it is preferable that the sealing composition contains 3 mass % or more of inorganic filler based on the total solid content, which causes a problem that the sealing film is difficult to use in electronic devices that require higher transparency. The present invention aims to provide a sealing film for electronic devices, which has a gas barrier layer made of an inorganic material laminated on one side of a substrate and an adhesive layer laminated in contact with the gas barrier layer, in which the adhesive layer has sufficient adhesion to the gas barrier layer and has high transparency. [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the inventors found that the above-mentioned problems could be solved by configuring the adhesive layer to contain an isobutylene-based polymer and a metal chelate compound and setting the haze ratio of the adhesive layer to 10% or less, and thus completed the present invention.
[0007] That is, the present invention relates to a sealing film for electronic devices, which comprises a gas barrier layer made of an inorganic material laminated on one surface of a substrate and an adhesive layer laminated in contact with the gas barrier layer, wherein the adhesive layer contains an isobutylene-based polymer and a metal chelate compound, and the haze ratio of the adhesive layer is 10% or less.
[0008] The haze ratio of the adhesive layer is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less. The total light transmittance of the adhesive layer is preferably 89% or more, and more preferably 90% or more. The storage modulus of the adhesive layer at 23° C. is 1.0×10 4 ~1.0×10 7 It is preferably in the Pa range.
[0009] The water vapor permeability of the electronic device sealing film is 15 g / m 2 Preferably less than one day. The adhesive layer preferably has an ultraviolet ray transmittance of 370 nm or less.
[0010] The content of the metal chelate compound is preferably in the range of 0.1 to 5.0 parts by mass, more preferably in the range of 0.4 to 2.0 parts by mass, and even more preferably in the range of 0.5 to 1.0 part by mass, based on 100 parts by mass of the isobutylene polymer. Effect of the Invention
[0011] The sealing film for electronic devices of the present invention has a high adhesive strength between the barrier layer and the pressure-sensitive adhesive layer, so that the electronic device can be kept under low humidity and low oxygen conditions. In addition, the sealing film for electronic devices of the present invention has high transparency, so that it can be applied to electronic devices that require high transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The sealing film for electronic devices of the present invention is a film comprising a gas barrier layer made of an inorganic material laminated on one surface of a substrate, and an adhesive layer laminated in contact with the gas barrier layer, the adhesive layer containing an isobutylene-based polymer and a metal chelate compound, and the haze ratio of the adhesive layer is 10% or less.
[0013] The substrate constituting the sealing film for electronic devices of the present invention is not particularly limited, and specific examples thereof include films or sheets made of resins such as polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, and polyesters such as polyethylene terephthalate, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resins, cycloolefin polymers, aromatic polymers, and polyurethane polymers.
[0014] Among these, those having gas barrier properties and transparency are preferred, and specific examples thereof include ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic polymers. The thickness of the substrate is not particularly limited, but from the viewpoint of ease of handling, it is preferably in the range of 0.5 to 500 μm, more preferably in the range of 1 to 200 μm, and even more preferably in the range of 5 to 100 μm.
[0015] The substrate may contain, as required, an ultraviolet absorber, a light stabilizer, an antioxidant, an antistatic agent, a slip agent, an antiblocking agent, a colorant, etc. Furthermore, as required, the substrate surface may be subjected to a surface treatment.
[0016] For the purpose of imparting gas barrier properties to the substrate, a gas barrier layer is laminated on the substrate directly or via another layer. The gas barrier layer is an inorganic film made of an inorganic material that can provide a desired gas barrier property. The inorganic film is not particularly limited, and specifically includes an inorganic vapor deposition film. More specifically, the inorganic vapor deposition film includes a vapor deposition film of an inorganic compound or a metal.
[0017] Raw materials for the vapor deposition film of the inorganic compound include inorganic oxides such as silicon oxide, aluminum oxide, magnesium oxide, zinc oxide, indium oxide, and tin oxide; inorganic nitrides such as silicon nitride, aluminum nitride, and titanium nitride; inorganic carbides; inorganic sulfides; inorganic oxynitrides such as silicon oxynitride; inorganic oxycarbides; inorganic carbide nitrides; and inorganic oxynitride carbides. Examples of materials for the metal vapor deposition film include aluminum, magnesium, zinc, and tin. These may be used alone or in combination of two or more.
[0018] Examples of methods for forming the inorganic vapor deposition film include PVD (physical vapor deposition) methods such as vacuum deposition, sputtering, and ion plating, and CVD methods such as thermal CVD (chemical vapor deposition), plasma CVD, and photo CVD.
[0019] The thickness of the gas barrier layer is not particularly limited, but from the viewpoints of gas barrier properties and ease of handling, it is preferably in the range of 10 to 2,000 nm, more preferably in the range of 20 to 1,000 nm, even more preferably in the range of 30 to 500 nm, and particularly preferably in the range of 40 to 200 nm. The gas barrier layer may be a single layer or multiple layers, but from the viewpoint of obtaining higher gas barrier properties, the gas barrier layer is preferably a multiple layer layer.
[0020] The water vapor permeability of the gas barrier layer is 0.5 g / m at 40° C. and 90% RH. 2 - 1 day or less is preferable, 0.05 g / m 2 The permeability of the gas barrier layer to water vapor and the like can be measured using a known gas permeability measuring device.
[0021] The pressure-sensitive adhesive layer constituting the sealing film for electronic devices of the present invention is laminated so as to be in direct contact with the surface of the gas barrier layer opposite to the substrate side. The adhesive layer contains an isobutylene polymer and a metal chelate compound, and has a haze ratio of 10% or less.
[0022] The isobutylene polymer has the effect of improving the moisture resistance of the adhesive layer while stably maintaining other physical properties. The polyisobutylene polymer is preferably in a solid state at room temperature (25° C.).
[0023] The isobutylene polymer is not particularly limited as long as it is a polymer mainly formed of a polyisobutylene skeleton and can obtain moisture permeability resistance, and specific examples thereof include homopolymers (single polymers) of isobutylene, copolymers obtained by copolymerizing isobutylene with olefin compounds such as 1-butene and 2-butene, and copolymers (block copolymers, random copolymers, graft copolymers) in which a segment skeleton consisting of one or more monomer components other than isobutylene, such as isoprene, styrene, butadiene, ethylene, propylene, acrylonitrile, vinyl chloride, vinyl bromide, hydrogenated styrene, pentadiene, cyclopentadiene, and dicyclopentadiene, is copolymerized in a polyisobutylene skeleton. These may be used alone or in combination of two or more.
[0024] The proportion of the polyisobutylene skeleton in the copolymer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more of the entire copolymer. The proportion of the polyisobutylene skeleton in the copolymer is preferably 90% by mass or less, more preferably 80% by mass or less of the entire polymer. The proportion of the segment skeleton consisting of a monomer component other than isobutylene in the copolymer is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 35% by mass or more of the entire copolymer. The proportion of the segment skeleton consisting of a monomer component other than isobutylene in the copolymer is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less of the entire copolymer.
[0025] More specifically, the isobutylene polymer may include Oppanol B10, 12, B15, N50, N80, N100, and N150 (manufactured by BASF), JSR Butyl 065, 268, and 365 (manufactured by JSR), Vistanex LMMS, LMMH, MML80, MML100, MML120, and MML140 (manufactured by Exxon Chemical), and SIBSTAR T102 (manufactured by Kaneka Corporation). These may be used alone or in combination of two or more.
[0026] The weight average molecular weight of the isobutylene copolymer is not particularly limited, but from the viewpoint of providing good coating properties and compatibility, it is preferably 4,000,000 or less, more preferably 3,000,000 or less. On the other hand, from the viewpoint of preventing repelling during coating of the composition for forming the adhesive layer, exhibiting moisture resistance of the adhesive layer, and improving mechanical strength, the weight average molecular weight is preferably 200,000 or more, more preferably 400,000 or more. The weight average molecular weight in the present invention can be determined by converting the molecular weight of standard styrene by gel permeation chromatography.
[0027] Specific examples of the metal chelate compound include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with ligands such as acetylacetone and ethyl acetoacetate. From the viewpoint of long-term storage stability, the polyvalent metal is preferably aluminum, and the ligand is preferably at least one of acetylacetone and acetoacetate.
[0028] More specifically, the metal chelate compound may be aluminum chelate compounds such as aluminum isopropylate, mono sec-butoxy aluminum diisopropylate, aluminum sec-butylate, aluminum ethylate, aluminum 9-octadecylacetoacetate diisopropoxide, aluminum ethylacetoacetate diisopropylate, aluminum ethylacetoacetate di-n-butylate, aluminum propylacetoacetate diisopropylate, aluminum n-butylacetoacetate diisopropylate, aluminum tris(ethylacetoacetate), aluminum monoacetylacetate bis(ethylacetoacetate), and aluminum tris(acetylacetonate); titanium tetraisopropoxide, titanium tetra-n-butoxide, titanium butoxy dimer, titanium tetra-2-ethylhexoxide, titanium allylacetoacetate triisopropoxide, and titanium di-n-butoxide (bis-2,4-pentanedioxy). onate), titanium diisopropoxide bis(tetramethylheptanedionate), titanium diisopropoxide bis(ethylacetoacetate), titanium methylphenoxide, titanium oxide bis(pentanedionate), titanium phosphate complex, titanium chelate compounds such as titanium octylene glycolate, zirconium tetra-n-propoxide, zirconium tetra-n-butoxide, zirconium allylacetoacetate triisopropoxide, zirconium di-n-butoxide Examples of the zirconium chelate compounds include zirconium diisopropoxide (bis-2,4-pentanedionate), zirconium diisopropoxide (bis-2,4-pentanedionate), zirconium diisopropoxide bis(tetramethylheptanedionate), zirconium diisopropoxide bis(ethylacetoacetate), zirconium butoxide (acetylacetate) (bisethylacetoacetate), zirconium tributoxymonoacetylacetonate, and zirconium stearate.
[0029] Among these, alkyl acetoacetate aluminum diisopropylate, aluminum monoacetylacetate bis(ethyl acetoacetate), and aluminum tris(acetylacetonate) are preferred from the standpoints of adhesive strength, transparency, and storage stability.
[0030] The content of the metal chelate compound is not particularly limited, but is preferably in the range of 0.1 to 5.0 parts by mass, more preferably in the range of 0.4 to 2.0 parts by mass, and even more preferably in the range of 0.1 to 1.0 parts by mass, relative to 100 parts by mass of the isobutylene polymer. If the content of the metal chelate compound is less than 0.1 part by mass, sufficient adhesive strength to the barrier layer cannot be obtained, and if it is more than 5.0 parts by mass, the gas permeability tends to increase.
[0031] The adhesive layer of the present invention has a haze ratio of 10% or less. The method of making the haze ratio 10% or less is not particularly limited, but for example, a method of not including an additive that causes an increase in the haze ratio in the adhesive layer can be mentioned. Specific examples of additives that cause an increase in the haze ratio include inorganic fillers and the like. Specific examples of the inorganic fillers include inorganic compounds that are added to the adhesive layer for the purpose of imparting moisture permeability resistance, and more specifically, silica such as nanosilica; metal oxides such as magnesium oxide, strontium oxide, aluminum oxide, and barium oxide; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; metal carbonates such as calcium carbonate and magnesium carbonate; metal nitrides such as aluminum nitride and titanium nitride; metal titanates such as barium titanate, strontium titanate, calcium titanate, magnesium titanate, and bismuth titanate; metal zirconates such as barium zirconate and calcium zirconate; aluminum borate; mineral fillers such as natural or synthetic clay and organically modified clay.
[0032] In addition, "additives that cause an increase in the haze ratio are not contained in the adhesive layer" means that the adhesive layer does not contain an amount of the additive that would cause the haze ratio to exceed 10%, and additives that cause an increase in the haze ratio can be contained as long as the haze ratio is within the range of 10% or less.
[0033] The adhesive layer may contain other additives as necessary. Specific examples of such additives include colorants such as pigments and dyes; surfactants; plasticizers; terpene-based tackifying resins, terpene-phenol-based tackifying resins, rosin-based tackifying resins, hydrogenated terpene-based resins, aromatic modified terpene-based resins, coumarone resins, indene resins, petroleum resins (aliphatic petroleum resins, hydrogenated alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic copolymer petroleum resins, alicyclic petroleum resins, dicyclopentadiene-based petroleum resins, hydrogenated dicyclopentadiene-based petroleum resins, etc. tackifiers; softeners such as mineral oil-based softeners, vegetable oil-based softeners, subfactise, fatty acids, fatty acid salts, synthetic organic compounds, and synthetic oils; organic fillers such as rubber particles, silicone powder, nylon powder, and fluororesin powder; antifoaming agents or leveling agents such as silicone-based, fluorine-based, and polymer-based agents; adhesion imparting agents such as triazole compounds, thiazole compounds, triazine compounds, and porphyrin compounds; thickeners such as Orben and Bentone; surface lubricants; rework improvers; antioxidants; anti-aging agents; light stabilizers; rust inhibitors; and ultraviolet absorbers.
[0034] In order to suppress deterioration of electronic devices due to light, the adhesive layer preferably contains an ultraviolet absorbing agent, specifically, a triazine-based ultraviolet absorbing agent, a benzotriazole-based ultraviolet absorbing agent, a benzophenone-based ultraviolet absorbing agent, an oxybenzophenone-based ultraviolet absorbing agent, a salicylic acid ester-based ultraviolet absorbing agent, a cyanoacrylate-based ultraviolet absorbing agent, or the like.
[0035] Among them, triazine-based ultraviolet absorbers or benzotriazole-based ultraviolet absorbers are preferred, and triazine-based ultraviolet absorbers are more preferred.Triazine-based ultraviolet absorbers may have at least one, preferably two, more preferably three hydroxyphenyl groups and / or alkoxy (methoxy, ethoxy, propoxy, etc.) phenyl groups in one molecule.In addition, benzotriazole-based ultraviolet absorbers may have at least one, preferably two hydroxyphenyl groups in one molecule.
[0036] Specific examples of triazine-based ultraviolet absorbers include 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN460, manufactured by BASF), a reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl and [(C10-C16 (mainly C12-C13) alkyloxy)methyl]oxirane (TINUVIN400, manufactured by BASF), and 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[3-(dodecyloxy)methyl]oxirane. )-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine with (2-ethylhexyl)-glycidic acid ester (TINUVIN 405, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN 1577, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA Corporation), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF Corporation), and the like.
[0037] Specific examples of benzotriazole-based ultraviolet absorbers include 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), ester compound of benzenepropanoic acid and 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-9 side chain and linear alkyl) (TINUVIN384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN900, manufactured by BASF), reaction product of methyl-3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 (TINUVIN1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, manufactured by BASF), 2(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN329, manufactured by BASF), -yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN329, BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate with polyethylene glycol 300 (TINUVIN213, BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN571, BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimido-methyl)-5-methylphenyl]benzotriazole (Sumisorb 250, manufactured by Sumitomo Chemical Co., Ltd.). The ultraviolet absorbents can be used alone or in combination of two or more.
[0038] The content of the ultraviolet absorber in the adhesive layer is preferably less than 15 parts by mass relative to 100 parts by mass of the isobutylene-based polymer, and more preferably 10 parts by mass or less, 7 parts by mass or less, 5 parts by mass or less, 3 parts by mass or less, 2.5 parts by mass or less, 2 parts by mass or less, 1.5 parts by mass or less, 1 part by mass or less, 0.8 parts by mass or less, 0.7 parts by mass or less, 0.6 parts by mass or less in the order of the left, and more preferably 0.5 parts by mass or less. The content of the ultraviolet absorber in the adhesive layer is preferably 0.1 parts by mass or more relative to 100 parts by mass of the isobutylene-based polymer.
[0039] The adhesive layer has excellent moisture permeability resistance. Specifically, the water vapor permeability of an adhesive layer having a thickness of 60 μm under an environment of a temperature of 40° C. and a relative humidity of 90% is 10 g / m 2 - 1 day or less is preferable, 6g / m 2 Less than 1 day is preferable, 3 g / m 2 1 day or less is even more preferable. The water vapor transmission rate of the adhesive layer can be measured in accordance with the method in the Examples. Note that since the value of the water vapor transmission rate of the adhesive layer depends on the thickness of the adhesive layer, if the thickness of the adhesive layer is not 60 μm, it can be calculated from the thickness. When the thickness is A μm and the water vapor transmission rate is B g / m 2 For an adhesive layer for one day, the water vapor transmission rate when the thickness is 60 μm can be calculated using the formula A × B / 60.
[0040] The storage modulus of the adhesive layer at 23° C. is 1.0×10 4 ~1.0×10 7 The storage modulus is preferably in the range of 1.0×10 Pa. 4 If the storage modulus is less than 1.0×10 Pa, sufficient adhesive strength with the barrier layer cannot be obtained. 7 If it is larger than Pa, re-peeling becomes difficult.
[0041] The adhesive layer preferably has a transmittance of 3% or less, more preferably 2% or less, and even more preferably 1% or less, for a 370 nm wavelength ultraviolet ray. If the transmittance of the adhesive layer for a 370 nm wavelength ultraviolet ray is greater than 3%, deterioration of electronic devices caused by ultraviolet rays cannot be sufficiently suppressed.
[0042] The composition for forming the adhesive (hereinafter sometimes referred to as "composition for forming an adhesive layer") can be prepared by a method of mixing and stirring an isobutylene-based polymer, a metal chelate compound, and other components as necessary in a solvent to dissolve or disperse the mixture in the solvent, or by melt-kneading an isobutylene-based polymer with a metal chelate compound and other components as necessary.
[0043] Examples of the solvent include aromatic hydrocarbon solvents such as benzene and toluene, ester solvents such as ethyl acetate and butyl acetate, ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone, aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane, alicyclic hydrocarbon solvents such as cyclopentane and cyclohexane, etc. These solvents can be used alone or in combination of two or more. The solid content concentration in the adhesive layer-forming composition is preferably in the range of 10 to 60% by mass, more preferably in the range of 10 to 45% by mass, and even more preferably in the range of 15 to 30% by mass.
[0044] The sealing film for electronic devices of the present invention is produced by laminating the pressure-sensitive adhesive layer so as to be in contact with the barrier layer of the substrate. The method for laminating the adhesive layer includes a method of melt-extrusion laminating the adhesive layer-forming composition directly on the barrier layer side surface of the substrate on which the barrier layer has been laminated in advance, a method of directly applying and drying the adhesive layer-forming composition on the barrier layer side surface of the substrate on which the barrier layer has been laminated in advance, etc. Alternatively, the method for laminating the adhesive layer includes a method of applying and drying the adhesive layer-forming composition on a release sheet, and then directly overlapping and pressing the adhesive layer formed on the release sheet and the barrier layer of the substrate on which the barrier layer has been laminated in advance, etc.
[0045] Specific examples of the method for applying the adhesive layer-forming composition include spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating. Specific examples of the drying conditions for drying the obtained sealing film include drying at 80 to 150° C. for 30 seconds to 5 minutes. The sealing film that has been subjected to the drying treatment may be left as it is for about one week to allow the adhesive layer to age. By allowing the adhesive layer to age, the adhesion between the adhesive layer and the gas barrier layer can be increased.
[0046] The thickness of the adhesive layer is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 25 μm or more. The thickness of the adhesive layer is not particularly limited, but is preferably 100 μm or less, more preferably 75 μm or less, and even more preferably 50 μm or less.
[0047] The water vapor permeability of the sealing film is 15 g / m 2 - 1 day or less is preferable, 10g / m 2 - 1 day or less is preferable, 5.0 g / m 2 15g / m 2 If it is longer than one day, the electronic device may be affected by moisture, e.g. dark spots may appear.
[0048] Specific examples of electronic devices that can be encapsulated with the encapsulating film of the present invention include organic devices such as organic transistors, organic memories, and organic EL elements; liquid crystal displays; electronic paper; thin film transistors; electrochromic devices; electrochemical luminescence devices; touch panels; solar cells; thermoelectric conversion devices; piezoelectric conversion devices; and electricity storage devices.
[0049] Among them, it can be suitably used for sealing flexible electronic devices in which electronic elements such as thin film transistors, LCD elements, LED elements, EL elements (organic EL elements, inorganic EL elements), solar cells, etc. are formed on a thin plastic substrate (plastic film). Specific examples of the thin plastic substrate (plastic film) for flexible electronic devices include poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT), poly(ethylene naphthalate) (PEN), polycarbonate (PC), polyimide (PI), liquid crystal polymer (LCP), cycloolefin polymer (COP), polysulfone (PSO), poly(p-phenylene ether sulfone) (PES), etc. The sealing film of the present invention exhibits excellent adhesion to the plastic film.
[0050] Examples of a method for sealing the flexible electronic device using the sealing film of the present invention include a method of sealing by adhering the adhesive layer surface of the sealing film to an adherend such as an electrode of an organic EL element and the plastic substrate (plastic film), and a method of using two of the sealing films to sandwich the flexible electronic device with the adhesive layer surfaces of the sealing films facing each other.
[0051] In a flexible electronic device sealed with the sealing film of the present invention, since the electronic elements of the electronic device are covered with the sealing film, the intrusion of moisture, etc. is suppressed. In addition, the adhesion between the adhesive layer and the substrate is not reduced due to vibrations, etc., during operation of the electronic device, so the intrusion of moisture, etc. is suppressed. EXAMPLES
[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES
[0053] 100 parts by mass of an isobutylene polymer, 0.5 parts by mass of a metal chelate compound, and 0.5 parts by mass of an ultraviolet absorber were stirred and dissolved in 160 parts by mass of toluene to obtain an adhesive layer-forming composition solution 1.
[0054] The obtained adhesive layer-forming composition solution 1 was applied onto a peelable PET film so that the thickness after drying would be 25 μm, and dried in an air bath at 100° C. for 3 minutes to obtain a laminate 1 having an adhesive layer. A peelable PET film was thermally laminated onto the adhesive layer of the obtained laminate 1 at 100° C. to obtain an adhesive sheet 1. EXAMPLES
[0055] An adhesive sheet 2 was obtained in the same manner as in Example 1, except that 1.0 part by mass of the metal chelate compound was used.
[0056] [Comparative Example 1] Comparative adhesive sheet 1 was obtained in the same manner as in Example 1, except that no metal chelate compound was used.
[0057] [Comparative Example 2] Comparative adhesive sheet 2 was obtained in the same manner as in Example 2, except that an acrylic adhesive was used instead of the isobutylene polymer.
[0058] [Comparative Example 3] Furthermore, a comparative adhesive sheet 3 was obtained in the same manner as in Example 1, except that 3.0 parts by mass of iron-based filler was added.
[0059] The obtained adhesive sheets 1 and 2 and comparative adhesive sheets 1, 2, and 3 (hereinafter sometimes referred to as "adhesive sheet 1, etc.") were evaluated by the following method. <Moisture permeability test> The obtained adhesive sheet 1 etc. was cut to a width of 210 mm and a length of 300 mm, the peelable PET films on both sides were peeled off, and a 25 μm thick PET film was attached to both sides of the adhesive sheet using a roller, and then autoclaved for 10 minutes under conditions of 80°C and 0.5 MPa to obtain a test specimen. The obtained test piece was subjected to measurement in a moisture permeability cup prepared according to JIS Z 0208 (Condition B: 40±0.5° C., 90±2% RH). The obtained result was taken as the moisture permeability.
[0060] <Total light transmittance and haze rate> Measurement was performed according to JIS K 7361 using a spectroscopic haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0061] <Peel strength test after leaving at 23℃ for 1 day> The obtained adhesive sheet 1 etc. was cut to 25 mm wide x 150 mm long, one side of the supported peelable PET film was peeled off, and then it was attached to a 100 μm thick PET film (26 mm wide x 160 mm long) using a roller. Then, autoclave treatment was performed for 10 minutes under conditions of 80 ° C and 0.5 MPa. The other peelable PET film was peeled off, and the adhesive sheet 1 etc. was attached to a glass plate using a roller, and left to stand overnight under conditions of 23 ° C and 50% RH to obtain a test piece. The obtained test piece was peeled off with a tensile tester at a speed of 300 mm / min and a peel angle of 180 °, and the obtained peel strength was taken as the adhesive strength.
[0062] <Measurement of storage modulus (G')> The peelable PET film of the obtained adhesive sheet 1 was peeled off and stacked to prepare an adhesive sheet sample having a width of 50 mm, a length of 50 mm, and a height of 2 mm. The adhesive sheet sample was cut into a circle having a diameter of 8 mm to obtain a test piece. The dynamic viscoelasticity of the obtained test piece was measured using a viscoelasticity measuring device (Disco-veryHR-2, manufactured by TA Instruments) to obtain the storage modulus G' at 23°C. The measurement was performed under the following conditions. Applied frequency: 10Hz Normal stress: 0.4N Heating rate: 5℃ / min
[0063] <UV transmittance> After peeling off one side of the peelable PET film carrying the obtained adhesive sheet 1, etc., the sheet was attached to a slide glass, and the ultraviolet transmittance at a wavelength of 370 nm was measured using a UV-visible spectrophotometer (UV-1900, manufactured by Shimadzu Corporation).
[0064] The evaluation results are summarized in Table 1.
[0065] [Table 1]
[0066] As is clear from the examples and comparative examples, it was found that sufficient adhesion to inorganic films such as glass can be obtained by using a metal chelate compound. It was also found that the adhesive strength during heating can be maintained even in a heated atmosphere. In addition, when a resin other than an isobutylene-based resin was used, the same effect as that of the present invention was not obtained, and sufficient moisture permeability was not obtained. [Industrial Applicability]
[0067] The encapsulating film of the present invention is useful as an encapsulating agent for electronic devices, and can be utilized in the field of manufacturing various electronic devices.
Claims
1. A sealing film for electronic devices, comprising a gas barrier layer made of an inorganic material laminated on one surface of a substrate, and an adhesive layer laminated in contact with the gas barrier layer, The adhesive layer comprises an isobutylene-based polymer and a metal chelate compound, and the haze ratio of the adhesive layer is 10% or less.
2. The sealing film for electronic devices according to claim 1 , wherein the adhesive layer has a haze ratio of 5% or less.
3. The sealing film for electronic devices according to claim 1 , wherein the adhesive layer has a haze ratio of 3% or less.
4. The sealing film for electronic devices according to claim 1 , wherein the adhesive layer has a total light transmittance of 89% or more.
5. The sealing film for electronic devices according to claim 1 , wherein the adhesive layer has a total light transmittance of 90% or more.
6. The storage modulus of the adhesive layer at 23° C. is 1.0×10 4 ~1.0 x 10 7 The electronic device sealing film according to any one of claims 1 to 5, wherein the viscosity is in the range of Pa.
7. The water vapor permeability of the sealing film for electronic devices is 15 g / m 2 The sealing film for electronic devices according to any one of claims 1 to 5, wherein the shelf life is one day or less.
8. The sealing film for electronic devices according to any one of claims 1 to 5, wherein the adhesive layer has an ultraviolet ray transmittance of 370 nm in wavelength of 3% or less.
9. The sealing film for electronic devices according to any one of claims 1 to 5, wherein the content of the metal chelate compound is in the range of 0.1 to 5.0 parts by mass based on 100 parts by mass of the isobutylene polymer.
10. The sealing film for electronic devices according to any one of claims 1 to 5, wherein the content of the metal chelate compound is in the range of 0.4 to 2.0 parts by mass based on 100 parts by mass of the isobutylene polymer.
11. The sealing film for electronic devices according to any one of claims 1 to 5, wherein the content of the metal chelate compound is in the range of 0.5 to 1.0 part by mass based on 100 parts by mass of the isobutylene polymer.
Citation Information
Patent Citations
Sealing composition
WO2019189723A1